Direct and Indirect Regulation of Spinal Cord Ia Afferent Terminal Formation by the γ-Protocadherins - Prasad, Tuhina; Weiner, Joshua A. (Frontiers in Molecular Neuroscience, 2011)
The Pcdh-γ gene cluster encodes 22 protocadherin adhesion molecules that interact as homophilic multimers and critically regulate synaptogenesis and apoptosis of interneurons in the developing spinal cord. Unlike interneurons, the two primary components of the monosynaptic stretch reflex circuit, dorsal root ganglion sensory neurons and ventral motor neurons (MNs), do not undergo excessive apoptosis in Pcdh-γdel/del null mutants, which die shortly after birth. However, as we show here, mutants exhibit severely disorganized Ia proprioceptive afferent terminals in the ventral horn. In contrast to the fine net-like pattern observed in wild-type mice, central Ia terminals in Pcdh-γ mutants appear clumped, and fill the space between individual MNs; quantitative analysis shows a ~2.5-fold increase in the area of terminals. Concomitant with this, there is a 70% loss of the collaterals that Ia afferents extend to ventral interneurons (vINs), many of which undergo apoptosis in the mutants. The Ia afferent phenotype is ameliorated, though not entirely rescued, when apoptosis is blocked in Pcdh-γ null mice by introduction of a Bax null allele. This indicates that loss of vINs, which act as collateral Ia afferent targets, contributes to the disorganization of terminals on motor pools. Restricted mutation of the Pcdh-γ cluster using conditional mutants and multiple Cre transgenic lines (Wnt1-Cre for sensory neurons; Pax2-Cre for vINs; Hb9-Cre for MNs) also revealed a direct requirement for the γ-Pcdhs in Ia neurons and vINs, but not in MNs themselves. Together, these genetic manipulations indicate that the γ-Pcdhs are required for the formation of the Ia afferent circuit in two ways: First, they control the survival of vINs that act as collateral Ia targets; and second, they provide a homophilic molecular cue between Ia afferents and target vINs.